2020
DOI: 10.1172/jci131540
|View full text |Cite
|
Sign up to set email alerts
|

Microphthalmia transcription factor expression contributes to bone marrow failure in Fanconi anemia

Abstract: Fancd2-/and WT MEFs, but clearly lower in these cells than in Fanca-/or Fancc-/-MEFs (Figure 1F and data not shown). Together, our previous data robustly demonstrate that loss of function of key components of the FANC core complex is associated with high expression of MiTF at both the RNA and protein levels. SMAD and p38 signaling pathways are necessary but not sufficient to activate MiTF expression in FA MEFs. The increase in Mitf expression in FANC pathway-deficient MEFs with increasing time in the same cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Another example of how MiTF deregulation can impact BM homeostasis was reported in a recent study we published on Fanconi anaemia (FA) [ 121 ]. FA, a rare genetic syndrome presenting developmental abnormalities of the skeleton, BM failure, leukaemia predisposition and genetic instability, is due to the loss-of-function of at least one of more than 22 genes that encode proteins constituting a major nuclear pathway involved in DNA repair and replication safeguards and rescue [ 11 , 39 , 115 ].…”
Section: Mitf Expression and Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of how MiTF deregulation can impact BM homeostasis was reported in a recent study we published on Fanconi anaemia (FA) [ 121 ]. FA, a rare genetic syndrome presenting developmental abnormalities of the skeleton, BM failure, leukaemia predisposition and genetic instability, is due to the loss-of-function of at least one of more than 22 genes that encode proteins constituting a major nuclear pathway involved in DNA repair and replication safeguards and rescue [ 11 , 39 , 115 ].…”
Section: Mitf Expression and Activitymentioning
confidence: 99%
“…More importantly, in contrast with the transient p38/MiTF activation observed during stress-induced haematopoiesis, we demonstrated that the p38/MITF axis is constitutionally active and associated with BMF in Fanca −/− mice. Supporting the notion that the unscheduled and constitutional activation of the p38/MiTF axis has pathological consequences, p38 inhibition or siRNA-mediated depletion of MiTF was sufficient to rescue HSCs defects in the Fanca −/− mice [ 121 ]. The previous observations shed light on two important physiologic aspects of the biology of both MiTF and FA.…”
Section: Mitf Expression and Activitymentioning
confidence: 99%
“…These mutations can cause downstream DNA damage accumulation and increased chromosome breakage, resulting in BMF. BMF has been attributed to hematopoietic stem cell (HSC) exhaustion and is paradoxically associated with hyperproliferation of hematopoietic stem and progenitor cells (HSPCs) and overactivation of several growth inhibitory pathways, including the p53, TGFb, and TNFa signaling pathways (Briot et al, 2008;Ceccaldi et al, 2012;Oppezzo et al, 2020;Rosselli et al, 1994;Walter et al, 2015;Zhang et al, 2016).…”
Section: In Translationmentioning
confidence: 99%
“…How MYC-dependent transcriptomic landscapes participate in the replication fork regulation likewise remains to be elucidated. Interestingly, MYC belongs to the same family of transcription factors as MiTF, which is highly expressed in FA HSPCs (Oppezzo et al, 2020). It would be interesting to see not only how MiTF behaves in the reported gradient but also if it changes in response to (+)-JQ1.…”
Section: In Translationmentioning
confidence: 99%
“…However, FANCA is dispensable for optimal FANCD2/ FANCI monoubiquitination (12), and several BMF-associated mutations of FANCA do not lead to DNA damage hypersensitivity (13)(14)(15), suggesting that FANCA affects BM homeostasis by also participating in pathways other than the DNA repair network. Beyond the DNA repair/DDR, the FANC pathway has been associated with several other cellular and systemic biological activities (16), including proinflammatory cytokine production and responses (17)(18)(19)(20), transcription (21)(22)(23), mRNA splicing (24), and reactive oxygen species metabolism (25)(26)(27), and its failure extends further than BMF to developmental abnormalities, cancer predisposition, and chromosomal instability.…”
Section: Introductionmentioning
confidence: 99%